الإستراتيجية التنافسية ودورها في تحقيق الميزة التنافسية في المؤسسة الإقتصادية - حراثي, زكرياء (My University, 2019)
In the business environment variable, longer competitive position of the institution of paramount importance, institutions can not get to keep the opportunity leadership in the market compared to competitors, unless possessed competitive advantages non-tradition and simulation, and that depends on the development and continuous improvement have this hand of On the other hand if you were able to conduct their resources in the best way, because the traditional sources of competitive advantage is no longer able to ensure the continuity of the institution. Keywords: strategy, strategy management, the competitive, competitive strategies, competitive advantage.
إتصالات الجزائر فرع مستغانم
Keywords: الإستراتیجیة، الإدارة الإستراتیجیة، المنافسة، الاستراتیجیات التنافسیة ،الميزة التنافسیة.إتصالات الجزائر فرع مستغانم